Psychosocial Aspects of Covid-19 and Self-confidence: we can beat it - Khan, Hamzullah (Infectious Diseases Journal of Pakistan, 2022)
Background & Objectives: During the outbreak of the pandemic COVID-19, there is urgent need for intervention to protect the victims and their family members, high risk individuals, health care workers from the secondary mental health crises associated with the disease. In vague of the above-mentioned rationale we did a survey to assess the psychosocial aspects of the COVID-19 and level of self-confidence of the respondents in centre based study. Material & Methods: A cross-sectional survey was conducted in March 2020. A total of 82 of the respondents were selected via convenient sampling, irrespective of age and gender for their knowledge of psychosocial impacts of COVID-19. Relevant information’s regarding the impact of COVID-19 on mental health was collected on a pre-designed proforma prepared in accordance with the objectives of the study. Results: The minimum age of the respondents was 20 years with a maximum of 50years. The mean with standard deviation of the respondents was 51+13 years. Thirty-Four (41.5%) were qualified practitioner with medical qualification and 48 (58.5%) were medical students and non medics. We observed a significantly higher difference in opinion of male gender (vs female gender) regarding their level of confidence in the fight against COVID-19 (p=0.02,OR=4.5),panic and anxiety they had (p=0.001, OR=0.12)and expectations from government in current situation(p=0.01,OR=3.9). It was observed that male gender is more of favor of ban on videos related to COVID patients as compared to female gender (p-0.005). The fear regarding the shortage of food was not significantly higher in both genders (p-0.724). The level of confidence in both genders insignificantly differ (0.03). Furthermore, the fear regarding the shortage of food was more in the youngsters (age=20-30 years) (p-0.03). Majority of the youngster and adult age responders were confident based on their spiritual guidance of religion and adopting the precautionary measure that they can beat Covid-19 (p- 0.048). Conclusion: We received a significant response of the respondents with higher level of self confidence, motivation and will to fight COVID-19. Although the respondents admitted that COVID- 19 has disturbed their daily routine and income but they were committed that they will win the battle against COVID-19. Key words: COVID-19, Confidence, Anxiety, Depression